2017
DOI: 10.1016/j.seppur.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

New insights in reactive extraction mechanisms of organic acids: An experimental approach for 3-hydroxypropionic acid extraction with tri-n-octylamine

Abstract: A detailed study of 3-hydroxypropionic acid (3-HP) reactive extraction with tri-n-octylamine (TOA) is proposed for the first time. It aims at uncovering some solvent-solutes interactions and providing global mechanisms to better understand and design the reactive liquid-liquid extraction of 3-HP in a biotechnological process. Eleven solvents of similar molecular sizes and several chemical types (alcohols, esters and alkanes) were investigated to understand their role on the extraction ability. Alcohols were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…Chen and Lee used a biocompatible organic phase composed of 20% Alamine 336, 40% oleyl alcohol and 40% kerosene by volume, for extractive fermentation of lactic acid. They obtained a partition coefficient of 0.30, lower than the one obtained in this study with the selected organic phase ( K D = 0.95 ± 0.004), but it allowed continuous acid extraction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen and Lee used a biocompatible organic phase composed of 20% Alamine 336, 40% oleyl alcohol and 40% kerosene by volume, for extractive fermentation of lactic acid. They obtained a partition coefficient of 0.30, lower than the one obtained in this study with the selected organic phase ( K D = 0.95 ± 0.004), but it allowed continuous acid extraction.…”
Section: Resultsmentioning
confidence: 99%
“…5 Although this pathway passes through 3-hydroxypropionaldehyde (3-HPA) production as an intermediate, which is toxic for the strain, 6 its In situ extraction occurs with a direct contact between the cells and the extraction phase: (a) two-phase partitioning bioreactors [11][12][13] or (b) solvent-impregnated particles dispersed in bioconversion medium 14,15 or with an indirect contact: (c) using immobilized cells in the bioconversion broth 16,17 ; or (d) using membrane-based extraction inside the bioreactor. 18,19 In-stream extraction occurs with direct contact: (e) pumping bioconversion broth to a column packed with solvent-impregnated particles 20 or indirect contact: (f ) membrane-based extraction outside the bioreactor 21,22 ; or (g) introducing a microfiltration unit to separate the biocatalyst from broth before contact. 23,24 accumulation in the medium can be avoided by progressively supplying glycerol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for similar acids such as pyruvic acid and lactic acid, a good extraction system for 3‐HP is tri‐ n ‐octylamine (TOA) in n ‐decanol (decanol). Indeed, we previously showed that the solvating power of decanol leads to high extraction yields . In this system, the main reaction occurring is ()AHnormalaq+()TOAnormalorg(),TOAH+normalAnormalorg …”
Section: Introductionmentioning
confidence: 90%
“…Reactive extraction has been studied and applied in various systems, either in liquid-liquid system [4], solidfluid system [5] and gas-liquid-liquid system [6]. In practical terms, reactive extraction is commercially applied in separation of metals [7][8], separation of intermediates [9][10], separation of organic acids [11][12], separation of vitamins [13], separation of lignin [14][15][16], synthesis of biodiesel [17] and preparation of green oxidants such as hydrogen peroxide [6].…”
Section: ■ Introductionmentioning
confidence: 99%